HUBUNGAN POLA ASUH ORANGTUA DENGAN MOTIVASI BELAJAR SISWA KELAS VIII DI SMP BAHRUL ULUM KOTA BOGOR - Permatasari, Desi; Makarim, Chodidjah (Universitas Islam Negeri Alauddin Makassar, 2020)
In the learning process, motivation is needed, because someone who does not have motivation to learn will not be able to carry out learning activities. In shaping learning motivation, parents play an important role in parenting their children. Parenting patterns play an important role in the success of an education. Therefore, this study aims to determine how parenting styles with the learning motivation of grade VIII students at SMP Bahrul Ulum Bogor City. This study uses a quantitative approach. The data collection technique used in this study was a questionnaire. The subjects of this study were students of class VIII at SMP Bahrul Ulum Bogor, totaling 24 students. The data analysis technique used in this study was to use SPSS 22 for Windows.Based on the results of the analysis above, it can be concluded that the correlation value of the X and Y variables is 0.755, when viewed from the interpretation table the value obtained is 0.755 which lies between 0.70 - 0.90. Judging from the data interpretation, including strong correlation. Then by looking at the table value on